Implementation of Character-Based Child-Friendly Schools in Fulfilling Student Rights at SDN Gembongan - Nurazizah, Ismi; Apriani, An-Nisa (Journal of Islamic Education and Ethics, 2024)
Education is a right for all citizens, especially in Indonesia. The state itself has a legal basis to guarantee the rights that must be obtained while in an educational environment, one of which is avoiding violence, both physical and verbal. The facts in the field are that there are still many cases of rights violations, such as bullying, which can threaten children's safety. This requires every educational institution to have a program anticipating rights violations. This research aims to determine the implementation of character-based, child-friendly schools and their impact on fulfilling students' rights, especially in grade 5 at SDN Gembongan. This research was carried out using a qualitative approach, which used data collection techniques in the form of observation, interviews, and documentation. The data sources were primary and secondary, with research subjects being principals, teachers, students, and parents. The data analysis technique was carried out in three steps, namely data reduction, data presentation, and drawing conclusions. The results of this research explained that the implementation of child-friendly schools at SDN Gembongan is carried out through preparation, planning, implementation, and evaluation steps. The implementation of character-based, child-friendly schools has been carried out quite well and positively impacts fulfilling students' rights. This can be seen in the emergence of mutual respect among students, which can reduce bullying and violence at school. There is adequate infrastructure, educators trained in children's rights, and schools implementing anti-violence policies. Child-friendly schools are a very suitable program that can be used to guarantee students' rights during learning activities.